Strategi Pengembangan SDM Petani Padi untuk Meningkatkan Hasil dan Kualitas Pertanian - Purdawan Purdawan; Ambardi Ambardi; Yayat Sujatna (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the strategy for developing human resources (HR) of rice farmers in Bonisari village to improve agricultural yields and quality and to determine the extent of the role of human resources of rice farmers in improving agricultural yields and quality, and to determine what factors can affect the quality and yield of rice farming in Bonisari village, Pakuhaji district, Tangerang regency. This study uses a qualitative approach with a field study research method, using primary and secondary data forms. In this study, the subjects of the study were farmers in Bonisari village, using 10 rice farmers as a sample from a total farmer population of 150 people. Data collection was carried out through interviews, observations, and documentation. The results of the study showed that the role of human resources (HR) of rice farmers in Bonisari village, Pakuhaji district has a major influence on the yield and quality of the rice harvest. While other factors are the area of ​​land and the type of rice seeds used. The results of the study also showed that the experience of rice farmers in Bonisari village was not so significant in influencing agricultural income.